Solving Linear Program with Simplex Method through App Calculator Simplex - Fadlan Alkhairi; Kasa Inti Josia Tambunan; Naila Fauziah; Sabrina Aisyah Putri Barus; Erlinawaty Simanjuntak (International Journal Labs, 2022)
Since the simplex approach takes so long to work, many students make mistakes or are just not as cautious as they should be, there is a learning material to help them overcome this. The objectives of this article are to accomplish the work of engineering ideas in Linear Program courses, gain insight into the development of learning media in the Linear Program, and be able to run digital media. This study was conducted in several ways, including using a line of inquiry, the graph technique, the simplex method, and Geogebra. The results reveal that the simplex calculator is uncomplicated to use and that the calculator's solutions are presented gradually and clearly. It is intended that by using this simplex calculator, students will be eligible to function more quickly.